Putative mechanisms of cognitive decline with implications for clinical research and practice. Issue 3 (18th January 2018) - Oliveira, Tadeu; Starkweather, Angela; Ramesh, Divya; Fetta, Joseph; Kelly, Debra Lynch; Lyon, Debra E.; Sargent, Lana
Abstract: Multiple intrinsic and extrinsic mechanisms contribute to vulnerability of cognitive decline and nurses play a significant role in assisting individuals and families to use strategies for healthy cognitive aging. The objective of this narrative review is to provide a synthesis of the intrinsic and extrinsic mechanisms of cognitive decline and conditions that are associated with cognitive decline. Well‐established intrinsic mechanisms of cognitive decline include aging, apolipoprotein E (APOE) ε4 carrier status, SORL1 mutations, neuroinflammation, mitochondrial dysfunction, amyloid deposition, and demyelination. Extrinsic risk factors include obesity, diabetes, hypertension, elevated lipid panel, metabolic syndrome, depression, traumatic brain injury, substance use, heart failure, and stroke. The various definitions of cognitive decline as well as the intrinsic and extrinsic factors that impact cognition as humans age should be incorporated in future clinical research studies. Nurses may use this information to help patients make lifestyle choices regarding cognitive health.